2006
DOI: 10.18438/b8ms3d
|View full text |Cite
|
Sign up to set email alerts
|

Effective Methods for Teaching Information Literacy Skills to Undergraduate Students: A Systematic Review and Meta-analysis

Abstract: Objective -The objective of this systematic review was to assess which library instruction methods are most effective for improving the information skills of students at an introductory, undergraduate level, using cognitive outcomes (measuring changes in knowledge). The study sought to address the following questions: 1) What is the overall state of research on this topic? 2) Which teaching methods are more effective?Methods -This project utilised systematic review methodology. Researchers searched fifteen dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 68 publications
4
65
0
Order By: Relevance
“…al., 2007;Koufogiannakis & Wiebe, 2006;Silver & Nickel, 2005) this preliminary study reaffirmed that exposure to IL instruction, regardless of method of deliveryeither through online modules or face-to-face librarian instruction-increases IL skills of students. Overall, for both groups there was an increase in test scores after online and face-toface instruction.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…al., 2007;Koufogiannakis & Wiebe, 2006;Silver & Nickel, 2005) this preliminary study reaffirmed that exposure to IL instruction, regardless of method of deliveryeither through online modules or face-to-face librarian instruction-increases IL skills of students. Overall, for both groups there was an increase in test scores after online and face-toface instruction.…”
Section: Discussionsupporting
confidence: 53%
“…Post-tests on material covered, including questions on confidence level and preferred mode of instruction, showed that there was no difference between the tutorial and classroom instruction in terms of quiz results (Silver & Nickel, 2005). Koufogiannakis and Wiebe's (2006) systematic review of 122 unique studies found that instruction provided electronically was just as effective as more traditional instruction. Specifically, "fourteen studies compared [Computer Assisted Instruction] CAI with traditional instruction (TI), and 9 of these showed a neutral result.…”
Section: Comparisons In Library Instructional Delivery Methodsmentioning
confidence: 99%
“…Portmann & Roush (2004) found that ILI increased library usage, though not library skills. One of Koufogiannakis and Wiebe's (2006) findings from their meta-analysis of ILI studies was that, overall, instruction of any variety was better than no instruction. Other research has focused on the effectiveness of particular interventions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the 1990s, growing interest in the effectiveness of library instruction has led to a variety of studies [7][8][9], but some of these have been duly criticized for variable quality. In addition, what seems missing is some investigation into what skills health librarians can bring to evidence-based practice (EBP) beyond information retrieval.…”
Section: Introductionmentioning
confidence: 99%